THE INFLUENCE OF PERSONALITY, WORK-LIFE BALANCE, AND ORGANIZATIONAL CULTURE ON JOB SATISFACTION (Case Study at PT BPR BKK DEMAK (Perseroda) KAB DEMAK): PENGARUH KEPRIBADIAN, WORK-LIFE BALANCE, DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA (Studi Kasus Pada PT BPR BKK DEMAK (Perseroda) KAB DEMAK) - Sofiya Ningsih; Tristiana Rijanti (LP2M Universitas Bina Mandiri Gorontalo, 2022)
This study explains how the influence of personality, work-life balance and organizational culture on job satisfaction (case study at PT BPR BKK DEMAK (Perseroda) KAB DEMAK). The population in this study were all employees at PT BPR BKK Demak as many as 120 employees and in collecting data using a questionnaire/questionnaire with a Likert scale. The analytical tool used is a validity test with a loading factor > 0.4, a reliability test with Cronbach Alpha > 0.7 and a multiple linear analysis test using the SPSS version 21 method. Based on the results of the analysis determined that: (1) Personality has a positive and significant effect on job satisfaction (2) Work-life balance has a positive and significant effect on job satisfaction (3) Organizational Culture has a positive and significant effect on job satisfaction. Keywords : Personality, Work-life Balance, Organizational Culture, and Job satisfaction